Pre- and post-Ebola outbreak trends in wild meat trade in West Africa - Funk, S.M.; Fa, J.E.; Ajong, S.N.; Eniang, E.A.; Dendi, D.; Vittorio, M. di; Petrozzi, F.; Amadi, N.; Akani, G.C.; Luiselli, L. (Elsevier, 2021)
Ebola virus disease, EVD, has been linked with wild meat. In Nigeria, strict restrictions on wild meat sales were applied after the first case in July 2014. We quantified wild meat trade in nine markets in southern Nigeria, during Oct. 2010 – Dec. 2019, and undertook consumer interviews during 2018–2019. Wild meat sales fell to low levels between during EVD (Jul. - Oct. 2014), after which Nigeria was declared Ebola-free. Prior to EVD (2012–2014), reptile carcass numbers declined markedly, collapsed during EVD, but rebounded immediately post-EVD until 2017 to values exceeding pre-EVD (especially true for turtles and tortoises). Reptile consumption increased as mammal numbers declined. After 2017, reptile numbers fell and remained low until the end of the study, indicating population collapses and depletion. Fruit bats and primates did not recover after EVD, but ungulates, rodents and carnivores increased significantly after EVD though never reached pre-EVD levels. Interviews revealed strong rural versus urban and age-specific differences regarding wild meat consumption and attitudes. Most people worried about Ebola and more than half of interviewees agreed that wild meat poses a transmission risk. Except urban males, over-60-year olds were least informed about the Ebola risk of wild meat, indicating that any future behavioural change campaign should focus on the younger age classes. Unlike other studies, our research clearly shows that changes in purchasing behaviour of consumers and education campaigns were effective in reducing the trade of bats and primates, animal groups likely to be implicated in the transmission of Ebola.